Karakteristik Vegetasi di Hutan Alam Dataran Rendah, Hutan Tanaman, dan Lahan Pasca Tambang Nikel di Kabupaten Bombana - Purnama Ardiyansyah; Basuki Wasis; Iwan Hilwan (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2019)
Nickel mining in Bombana District is one of the mining activities which generates a very large income for the area. However, mining carried out continuously will certainly cause the environment to be damaged, especially soils and vegetation when mining activities end. Good management of post-mining land is one of the obligations of the mining business unit. Management can include reclamation and replanting land so that exposed land can be reforested. Reforesting ex-mining land is not easy. These efforts need to be carried out with comprehensive treatment concerning the improvement of the vegetation composition as well as the physical, chemical, and biological aspects of the soil used so that the greening plants that are introduced can adapt well. The purpose of this study is to identify and compare the characteristics of vegetation and soil in lowland natural forests, plantations and post-nickel mining in Bombana District. In this study, observations were made at three different locations to look for differences in characteristics caused by the existence of nickel mining activities. From the results of the study showed that there was a decrease in the composition of vegetation due to changes from natural forest to plantations. In addition, the level of soil fertility is also declining due to land clearing for mining. Key words : nickel, mining, Bombana, soil, vegetation